Dilema Etik bagi Tenaga Kesehatan dalam Menentukan Pilihan Tindakan Medis Berdasarkan Prinsip Berbuat Baik (Beneficence) atau Prinsip Otonomi (Autonomy) - Saputra, Warren; Djai Yen, Liauw (Universitas Kristen Krida Wacana, 2024)
The primary goal of the medical profession is to alleviate suffering and restore health to patients through medical practice. This practice is based on ethics and morals. The principle of beneficence requires doctors to act for the good of the patient, while the principle of autonomy emphasizes the individual's right to make their own decisions. These principles are prima facie obligations that in situations of conflict, must be assessed for their respective weight based on context to determine the best course of action for the patient. The literature review was conducted from the reference source, PubMed. The articles obtained were selected according to the inclusion criteria, and the final result obtained 10 articles. Beneficence and autonomy are key moral duties in bioethics, and the interaction between the two requires careful consideration in determining the best way to act. In some cases, such as the practice of allergy, ethical dilemmas may arise. Deepening the science of ethics and using appropriate communication with soft paternalism are options in the solution of such problems. In medical practice, the principles of beneficence and autonomy often pose dilemmas, especially when the doctor's preference to do good conflicts with the patient's medical decisions, such as in cases of physical restraints, plastic surgery, pediatric patients, and mental patients. Persuasive conversations can help achieve care that meets the patient's goals, without compromising the principles of beneficence and autonomy.